2013
DOI: 10.1002/ps.3635
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of pogostone against Spodoptera litura and Spodoptera exigua (Lepidoptera: Noctuidae)

Abstract: PO possesses strong insecticidal activities, especially antifeedant, larvicidal, growth inhibitory and pupicidal activities, against S. litura and S. exigua. PO may partly account for the insecticidal activity of patchouli oil and may be a promising candidate for the control of agricultural insects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 28 publications
3
37
1
1
Order By: Relevance
“…In the present study, different fractions showed pupicidal activity at concentration dependent manner. The present findings are in agreement with the findings of Huang et al [8] who reported that Pogostone from Pogostemon cablin (Blanco) Benth. (Lamiaceae) exhibited pupicidal activity against S. litura and S. exigua.…”
Section: Crude Extractssupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, different fractions showed pupicidal activity at concentration dependent manner. The present findings are in agreement with the findings of Huang et al [8] who reported that Pogostone from Pogostemon cablin (Blanco) Benth. (Lamiaceae) exhibited pupicidal activity against S. litura and S. exigua.…”
Section: Crude Extractssupporting
confidence: 83%
“…(Fabaceae) exhibited antifeedant, larvicidal and growth inhibitory activities (increased larval-pupal duration and pupicidal activity) against H. armigera and S. litura. Natural compound from Pogostemon cablin (Blanco) Benth (Lamiaceae) exhibited strong antifeedant and insecticidal activities against S. litura and S. exigua [8].…”
Section: Introductionmentioning
confidence: 99%
“…It also delayed pupal-adult ecdysis (when treated with root extracts) as compared to controls. The essential oil of the Pogostemon cablin plant, containing an active ingredient, pogostone, has been reported to cause prolongation of larval and pupal duration in the lepidopteran insect, Spodoptera exigua (Huang et al 2013). Extracts from different plants have been observed to increase larval, pupal and adult duration in several lepidopteran insects.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, its frequent outbreaks in the Asian have caused considerable agricultural economic losses and long-term use of synthetic pesticides that have resulted in serious resistance of S. litura against various insecticides (Tuan et al, 2013). Therefore, S. litura has been paid close attention with the studies extensive on its insecticidal toxicology (Gong et al, 2014;Meng et al, 2013), molecular mechanisms of its insecticide resistance (Rajagopal et al, 2002;Zhou et al, 2012) and new alternatives for its integrated management (Arasu et al, 2013;Huang et al, 2013;Zhao et al, 2013). In some of these cases, it was proofed that RNAi is a useful tool for studying genes function in S. litura.…”
Section: Introductionmentioning
confidence: 99%